Inovasi Media Flipbook Digital dalam Pembelajaran Menulis Carita Pondok di SMA - Alisha Hemalia; Usep Kuswari; Yatun Romdonah Awaliah; Sarip Hidayat (Advances In Education Journal, 2026)
The background of this study lies in the students' short story writing skills, which remain low. Therefore, innovative and creative learning media are required. The purpose of this study is to describe whether there is a difference in students' abilities before and after utilizing digital flipbook media. The method employed in this study was a pre-experimental study with a quantitative approach, using a one-group pretest-posttest design conducted on 26 students at a senior high school in Cimahi. The techniques used in this study were written pretest and posttest. The collected data were subsequently analyzed using SPSS Statistics 25, which included a normality test and a hypothesis test. Based on the research results, the students' short story writing skills before using the digital flipbook media were categorized as fair, with an average score of 67.69. Meanwhile, the students' short story writing skills after using the digital flipbook media were categorized as good, with an average score of 81.30. There was a difference in short story writing skills before and after using the digital flipbook media. The results of the hypothesis testing indicated that H1 was accepted and H0 was rejected. This means that there was a significant difference in the students' short story writing skills before and after using the digital flipbook media. Consequently, digital flipbook media is effective in the learning of short story writing.